Strategi Pengklasifikasian dan Peramalan Untuk Mengidentifikasi Permintaan Sparepart Bearing di PT Semen Indonesia (Persero) - Laxmi Ratnaningsih; Moch Tutuk Safirin (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT Semen Indonesia (Persero) Tbk. faces challenges in assessing the spare parts requirements of different units. The inability to prioritise procurement has led to overstocking of non-critical parts and shortages of essential parts. In addition, there are problems in fulfilling spare parts requests in a timely manner due to unpredictable demand patterns for certain items. Therefore, a systematic approach is needed to analyse spare parts demand characteristics using a combination of ABC, SDE and ADI-CV classifications and to evaluate the effectiveness of the Double Exponential Smoothing (DES) forecasting method. The classification results show that 47 spare parts items fall into the AS and AD categories, which are characterised by high investment values and long procurement lead times, making them top priorities. Demand pattern analysis revealed 42 items with lumpy patterns and irregular intervals, requiring further analysis to accurately estimate spare parts demand. The Double Exponential Smoothing (DES) forecasting method produced forecasts that closely matched actual demand. This combination of classification and forecasting methods effectively prioritises spare parts and optimises strategic decision making in spare parts procurement.